Motif Penggunaan Modem Orbit Telkomsel Pada Masyarakat di Kabupaten Karawang : Studi Fenomenologi Tentang Kebutuhan Internet - Wijaya, Ridho Tirto; Arindawati, Weni A. (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research aims to explore the motives and experiences of using the PT Orbit Modem. Telkom Indonesia Tbk. by the people of Karawang Regency in meeting internet needs. By using a qualitative approach and phenomenological study methods, this research identifies the factors that influence people's decisions in using the Telkomsel Orbit modem. Data was collected through in-depth interviews with ten informants who are Telkomsel Orbit modem users in Karawang Regency. The research results show that the motive for using the Telkomsel Orbit modem is influenced by previous positive experiences with Telkomsel products, trust in stable network quality, affordable prices, ease of use, and internet stability. The motives for using it include cost savings, efficiency of use, ease of installation, payment via the MyOrbit application, and the experience of internet stability for daily needs. Therefore, it can be concluded that the decision to use the Telkomsel Orbit modem by the people of Karawang Regency was driven by a combination of positive experiences and the desire to create better conditions in the future, with a focus on trust, efficiency and stability in internet use.